Reserve provision by CHP units and its impact on equilibria in spot and reserve markets - Christian Furtwängler; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance, 2018)
There is a broad consensus that the energy transition planned in Europe, along with an increasing share of renewable energy sources, demands a sufficient number of flexibility providers. The established flexibility procurement mechanisms, notably the reserve markets, are expected to reflect the cost of flexibility provision. As more flexibility is needed - given a higher resulting uncertainty of residual load levels - prices for such provision are expected to rise. In recent years, however, reserve provision prices in Germany have shown a decreasing tendency, with overall reserve demand remaining constant. This contribution proposes to analyse first the equilibrium pricing of reserve power against the electricity spot market in a stylized setting. A fundamental market model is used to analyse the price effects of reserve flexibility from Combined Heat and Power (CHP) entering both markets, using 2016 data as input. Four cases are analysed to assess the effects of different reserve market characteristics. In Case 1, CHP plants may not provide secondary reserve for the reserve market and a stylized heat demand curve is considered as operating restriction of CHP plants in the spot market. Case 2 allows reserve provision by CHP plants, but models these plants without heat restrictions. Case 3 considers the combination of the stylized heat demand curve and reserve from CHP plants. Case 4 extends Case 3 by 100 small CHP power plant pools, analysing their additional effect on reserve prices. From June 2018 on, secondary reserve in Germany will be auctioned in four-hour tenders, instead of the current weekly peak/off-peak auction design. We therefore compare the results to such an alternative auction regime with the same demand, but four-hour reserve provision tenders to reflect upcoming market design changes. Our approach leads to spot prices at a similar mean level compared to historical data, with MAE values in a range from 5.91-6.64 exteuro/MWh for all cases. The positive reserve price levels in this approach also compare to mean historical price levels. The price lowering effect of flexibility provision from CHP is clearly identifiable, underscoring the importance of explicit modelling of heat demand restrictions. A change of the reserve tender regime towards 4-hour tenders further lowers positive reserve prices in all cases. As a result, low reserve price levels may be expected to persist in the medium term despite the expected increase of intermitting generation.
Keywords: 330; Equilibrium pricing; flexibility provision; reserve markets; combined heat and power; heat restrictions